From fighting against death to commemorating the dead at Tangshan Earthquake heritage sites - Chen, Shengrong; Xu, Honggang (Journal of tourism and cultural change, 2018)
While previous studies have emphasized the social construction aspect in man-made disasters, this study applies this framework to natural disasters. By focusing on three different commemorative heritage sites of the 1976 Great Tangshan Earthquake, constructed over the years in China, we argue that similar to man-made disasters, the construction of natural disaster dark heritage is also influenced by political, social and cultural factors. From fighting against death to celebrating life, the representations of death in dark heritage sites are always changing, particularly in transitional China, and tourism has played a role in this dynamic process. Some of the key features of natural disaster dark heritage sites are also discussed.